Toward a systematic understanding of cancers: a survey of the pan-cancer study - Liu, Zhaoqi; Zhang, Shihua (Frontiers in Genetics, 2014)
Studies on molecular aberrations of cancer patients have increased unprecedentedly in scale and accessibility, allowing large-scale integrative cross-cancer analysis. Pan-cancer study is becoming a valuable paradigm for cancer genomics. Here, we review recent advances in this field and highlight the potential challenges and directions especially from the computational angle.